Ethics in canine reproduction – a survey among veterinarians who provide canine reproductive services - Arlt, Sebastian P.; Øvregaard, Helen (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective Several dog breeds suffer from health and welfare problems due to unfavorable anatomies and high prevalence of inherited diseases. Veterinarians should care for animal health and welfare but they may also be involved in breeding management including the use of reproductive techniques.Material and methods An online survey was conducted to find out how veterinarians who are involved in small animal reproduction regard ethical issues, which services they provide, how they discuss and handle ethical concerns and talk about them with breeders.Results In total, 83 participants mainly from Europe completed the online survey. Opinions on which interventions are ethical or not were heterogeneous. Most respondents (79.2 %) found it ethical to perform artificial insemination (AI) in dogs which did not reproduce naturally before. However, 62.7 % of participants stated that surgical insemination is not ethical. Elective cesarean sections are considered not ethical by approximately half of the participants. A closer look at responses to the questions of whether AI is ethical under specific conse quences suggests that most veterinarians are making ethical and value judgments in terms of what is justifiable or not. However, more than 80 % feel at least sometimes compromised by ethical conflicts.Clinical relevance This research intended to foster discussion of this topic. International strategies should be developed to support solving conflicts and dilemmas related to ethical issues in dog breeding and assisted reproduction, as well as diminishing physical disabilities and heritable diseases.
Keywords: Hundezucht; assistierte Reproduktion; Defektzucht; Tiergesundheit